2010
DOI: 10.21818/001c.17582
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Group Cognitive Complexity on Group Satisfaction: A Person-Environment Fit Perspective

Abstract: Thus, consideration of group characteristics in organizations is an important issue (Druckman & Bjork, 1991). In this study, the interactive influence of group cognitive complexity, task complexity, and group structure with satisfaction was analyzed. The findings suggest that when a task is complex, a decentralized structure leads to greater satisfaction than a centralized structure. Furthermore, groups lower in cognitive complexity were influenced more than complex groups by a mismatch between task complexity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
0
5
1
Order By: Relevance
“…Regarding the impact of task complexity and group structure on the relationship between GCC and group satisfaction, contrary to expectations, the findings reported by Mayer and Dale (2010) showed that groups with a lower level of GCC reported higher satisfaction when the task was complex and when the group structure was decentralized (i.e. all group members hold the decision-making authority and the communication flow is spread among all members), as compared to low GCC groups engaged in a less complex task and a decentralized structure.…”
Section: Composition Perspective On Group Cognitive Complexitycontrasting
confidence: 76%
“…Regarding the impact of task complexity and group structure on the relationship between GCC and group satisfaction, contrary to expectations, the findings reported by Mayer and Dale (2010) showed that groups with a lower level of GCC reported higher satisfaction when the task was complex and when the group structure was decentralized (i.e. all group members hold the decision-making authority and the communication flow is spread among all members), as compared to low GCC groups engaged in a less complex task and a decentralized structure.…”
Section: Composition Perspective On Group Cognitive Complexitycontrasting
confidence: 76%
“…To the best of our knowledge, only a few empirical studies have been conducted on the link between group job satisfaction and other constructs. Among these few studies, group job satisfaction is usually considered an antecedent (Fauth et al, 2013;Mason and Griffin, 2005) or consequence (Lester et al, 2002;Mayer and Dale, 2010;Zampetakis and Moustakis, 2011) rather than a moderator. These studies focused on the relationships between employee group-level variables (Fauth et al, 2013;Lester et al, 2002;Mayer and Dale, 2010;Mason and Griffin, 2005;Zampetakis and Moustakis, 2011).…”
Section: Job Satisfaction 221 Individual Job Satisfactionmentioning
confidence: 99%
“…Among these few studies, group job satisfaction is usually considered an antecedent (Fauth et al, 2013;Mason and Griffin, 2005) or consequence (Lester et al, 2002;Mayer and Dale, 2010;Zampetakis and Moustakis, 2011) rather than a moderator. These studies focused on the relationships between employee group-level variables (Fauth et al, 2013;Lester et al, 2002;Mayer and Dale, 2010;Mason and Griffin, 2005;Zampetakis and Moustakis, 2011). No research has been conducted on the relationships across group and individual levels.…”
Section: Job Satisfaction 221 Individual Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is based on person-environment (PE) fit theory and the transactional model of stress. Person-environment fit is the degree to which individual characteristics harmonise with those of his or her environment (Meyer & Dale, 2010). Person-environment fit theory and transactional model of stress assert that the interaction between an individual and his or her environment determines whether or not the situation is stressful for that person.…”
Section: Theoretical Frameworkmentioning
confidence: 99%